2011
DOI: 10.1016/j.ygyno.2011.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine SLPI secretion upregulates MMP-9 transcription and secretion in ovarian cancer cells

Abstract: Objectives Secretory leukocyte protease inhibitor (SLPI) is amplified in serous ovarian cancer. We have dissected its function, showing it is a survival factor for ovarian cancer and promotes tumorigenesis and paclitaxel-resistance. We hypothesized that the protease inhibitory function was responsible for modulating SLPI’s invasive capacity. Methods Stable HEYA8 ovarian cancer transfectants expressing vector, wild type SLPI, and protease inhibitor null (F-)SLPI were examined in vitro and in xenografts. Invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…SLPI modulates intracellular signaling pathways, such as NF-kB, ERK, and TGF-b, 32,33,43 and prevents synthesis of TNF-a and matrix metalloproteinases. 29,44,45 In line with published data, we detected diminished expression of IkBa and elevation of NFkB p65 after inhibition of SLPI (Figure 7). However, we did not detect any differences in TNF-a synthesis by hematopoietic cells deficient in SLPI.…”
Section: Discussionsupporting
confidence: 91%
“…SLPI modulates intracellular signaling pathways, such as NF-kB, ERK, and TGF-b, 32,33,43 and prevents synthesis of TNF-a and matrix metalloproteinases. 29,44,45 In line with published data, we detected diminished expression of IkBa and elevation of NFkB p65 after inhibition of SLPI (Figure 7). However, we did not detect any differences in TNF-a synthesis by hematopoietic cells deficient in SLPI.…”
Section: Discussionsupporting
confidence: 91%
“…There is a growing body of evidence demonstrating the tumorpromoting roles of WAP domain family members (6,7). Among these WAP genes is secretory leukocyte protease inhibitor (SLPI), which is also overexpressed in ovarian cancer (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Hoskins et al (8) reported that SLPI stimulated ovarian cancer invasion, modulated in part by its serine protease inhibitory activity. Significantly, comparative genomic hybridization studies have shown that 20q13 is among the most frequently amplified chromosomal regions in ovarian cancers (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting SLPI by siRNA induced apoptosis, and inhibited the migration and invasion of PDAC cells ( Zhang et al, 2015 ). SLPI was increased in ovarian cancer and enhances the invasiveness of ovarian cancer cells via modulating MMP-9 release ( Hoskins et al, 2011 ; Tsukishiro et al, 2005 ). In the previous study, SLPI was found overexpressed in colorectal cancer tissues of 296 CRC patients ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%